Dano and Alimanovic: the recent evolution of CJEU caselaw on EU citizenship and cross-border access to social benefits - Lanceiro, Rui (2017)
Since its inception, the concept of EU citizenship, as well as the rights and duties deriving therefrom, has evolved considerably, particularly in the area of social rights. ECJ case law has played a central role in defining the right of EU citizens to access social benefits in the host Member States, which meant a decrease in their degree of discretion to restrict the access to national social securities systems. However, the recent Dano and Alimanovic judgments represent a significant change from previous case-law, setting limits on the right of EU citizens to social benefits in the host Member States. The right of residence in another Member State appears to be dependent on the status of a worker citizen in accordance with the new methodology in order to avoid being an excessive burden on the social system of the host Member State. However, the new approach still leaves several unanswered questions. Were these decisions an attempt to address the “social security tourism” debate? Is the CJEU falling behind with regard to the protection of social rights? What will remain of previous jurisprudence?